Somali and Afghan diaspora associations in development and relief cooperation - Matilde Skov Danstrøm; Nauja Kleist; Ninna Nyberg Sørensen (Danish Institute for International Studies (DIIS), 2015)
[Objectives] The report is part of DIIS' Development Tendencies Studies commissioned by the Ministry of Foreign Affairs. The aim of the present report is to update knowledge related to diasporas as development actors in fragile situations. The report examines this issue through a focus on individual and collective remittances sent to the countries of origin and neighbouring areas, identifying specific concerns, opportunities and hindrances in relation to development and relief. It further examines case studies of two significant refugee and asylum seeking groups in Denmark, respectively Afghans and Somalis, with particular focus on their collective involvement in development projects. The Somali and Afghan diaspora cases have been chosen partly because both are important recipients of Danish development and humanitarian aid, partly because both constitute large groups of refugees in Denmark. In addition, Somalia and Afghanistan are the exclusive target countries of the Danish Diaspora Programme, a diaspora development cooperation initiative funded by Danida and managed by the Danish Refugee Council (DRC). [The report has the following objectives] * To provide an overview of how development cooperation initiatives can assist and upscale diaspora engagement and collective remittances in countries of origin and neighbouring areas. This includes focus on potential barriers, concerns and pitfalls. * To examine how and to what extent Somali and Afghan diaspora groups engage in collective development and reconstruction activities in their countries of origin and neighbouring areas, including focus on potential barriers, concerns and pitfalls from their perspective. * To identify lessons learned and provide policy recommendations for future cooperation.
Keywords: 300